Physicochemical Properties of Aphron Drilling Fluids - Wu, Xin-Min; Yan, Yong-Li (Asian Journal of Chemistry, 2010)
Colloidal gas aphrons were first reported by Sebba as micro bubbles (25-125 μm), composed of a gaseous inner core surrounded by a thin surfactant film, which are created by intense stirring of a surfactant solution. Since then, these colloidal dispersions have been used for diverse applications, with a particular focus on separation processes. However, exploitation of colloidal gas aphrons in petroleum industry is only an outset, which was first used in west Texas in 1998, called Aphron drilling fluid. This fluid is characterized as having in its continuous phase, high viscosity at low shear rate and containing, as internal phase, micro air or gas bubbles, non coalescing and recirculateable. In this paper, we illuminate the physical and chemical properties of aphron drilling fluid and its processing mechanism.